Between Life Cycle Model, Labor Market Integration and Discrimination: An Econometric Analysis of the Determinants of Return Migration - Eric Schuß (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the determinants of return migration by applying the Cox hazard model to longitudinal micro data from 1996 to 2012, including immigrants of a wide range of nationalities. The empirical results reveal the validity of the life cycle model of Migration Economics and a strong return probability decreasing effect of labor market integration and societal integration. Modeling non-proportional effects of qualification and obtaining social benefits supports the human capital thesis and supplies new insights with regard to the supranational European labor market and to development policy. At the beginning of residence highly qualified immigrants as well as immigrants obtaining social benefits display a rather high hazard ratio that, however, decreases each additional year of residence afterwards. Via survivor functions further remarkable results about adverse selection effects and about the interaction between qualification and labor market integration can be found. Finally the paper derives important policy implications from the empirical analysis.
Keywords: C41; J61; O15; 330